PENGARUH KEPRIBADIAN LIMA FAKTOR TERHADAP KESUKSESAN KARIR - Adiyono Adiyono; Ratno Purnomo; Wiwiek Rabiathul Adawiyah (Jurnal Bisnis dan Ekonomi, 2017)
The aims of the study are investigate and examine the effects of The Big Five Personalitytoward career success in thecontext of public sector organization. The scope of thisstudy is the entire of structural employeeson the tax office which is operating in Purwokerto, Cilacap, Purbalingga and Kebumen. The sample of data were taken from 188respondents. Proportionate stratifiedrandom sampling method was used to determine the respondents. Survey by questionnaire is applied in this study. The analysis tool in this study is regression analysis. Based on the results of hypothesis testing, there are four revelations: First, neuroticism has negative impact on subjective career success. Second, extroversion has positive effect on objective career success. Third, agreeableness has negative impact on objective and subjective career success. Fourth, openness to experience has negative impact on objective career success. The implication of this study is that personality is important in workplace because it can facilitate career. Organizations need to give special attention on the personality of employees including in recruitment process, training and employees development. Keywords: career, personality, the big five